Yes, Heather is correct. The expressions are not equivalent
<em><u>Solution:</u></em>
Given that,
Heather says, the following expressions are not equivalent
![4x - 2x + 8\ and\ 2(x-4)](https://tex.z-dn.net/?f=4x%20-%202x%20%2B%208%5C%20and%5C%202%28x-4%29)
Because one expression has a term that is subtracted and the other does not
<em><u>Combine the like terms in first expression:</u></em>
![4x - 2x + 8 = 2x +8](https://tex.z-dn.net/?f=4x%20-%202x%20%2B%208%20%3D%202x%20%2B8)
<em><u>Let us first expand the second expression</u></em>
By distributive property
a(b + c) = ab + bc
Therefore,
![2(x-4) = 2x - 8](https://tex.z-dn.net/?f=2%28x-4%29%20%3D%202x%20-%208)
<em><u>Thus the two expressions are:</u></em>
![2x + 8\ and\ 2x-8](https://tex.z-dn.net/?f=2x%20%2B%208%5C%20and%5C%202x-8)
Yes both the expressions are not equivalent
Because, in first expression 2x is added to 8
But in second expression, 8 is subtracted from 2x
Thus heather is correct